2013
DOI: 10.1038/onc.2013.126
|View full text |Cite
|
Sign up to set email alerts
|

MYC, a downstream target of BRD-NUT, is necessary and sufficient for the blockade of differentiation in NUT midline carcinoma

Abstract: NUT midline carcinoma (NMC) is an aggressive type of squamous cell carcinoma that is defined by the presence of BRD-NUT fusion oncogenes, which encode chimeric proteins that block differentiation and maintain tumor growth. BRD-NUT oncoproteins contain two bromodomains whose binding to acetylated histones is required for the blockade of differentiation in NMC, but the mechanisms by which BRD-NUT act remain uncertain. Here we provide evidence that MYC is a key downstream target of BRD4-NUT. Expression profiling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
188
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(198 citation statements)
references
References 39 publications
10
188
0
Order By: Relevance
“…Both MXD1 and MXD4 are members of the MAD gene family and regulate MYC , leading to cell growth in differentiating tissues 50. Grayson et al have identified that MYC is a key transcriptional target of BRD4–NUTM1 fusion and that dysregulation of MYC by BRD4–NUTM1 fusion has a central role in the pathogenesis of in NUT midline carcinoma 51. Our data revealed an increase in both NUTM1 mRNA and protein expression in tumor tissue.…”
Section: Discussionsupporting
confidence: 56%
“…Both MXD1 and MXD4 are members of the MAD gene family and regulate MYC , leading to cell growth in differentiating tissues 50. Grayson et al have identified that MYC is a key transcriptional target of BRD4–NUTM1 fusion and that dysregulation of MYC by BRD4–NUTM1 fusion has a central role in the pathogenesis of in NUT midline carcinoma 51. Our data revealed an increase in both NUTM1 mRNA and protein expression in tumor tissue.…”
Section: Discussionsupporting
confidence: 56%
“…BRD4-NUT nuclear foci correspond to chromatin-bound 'megadomains' that drive ectopic transcription in naïve cells BRD4-NUT associates with chromatin via the dual bromodomains of BRD4 (Dey et al 2003;French et al 2008;Grayson et al 2014), forming ∼80-100 large foci that can be visualized in interphase nuclei and metaphase chromosomes (Fig. 1A).…”
Section: Resultsmentioning
confidence: 99%
“…Approximately 80% of NMCs harbor a chromosomal translocation that fuses NUT to BRD3 or BRD4, which encode bromodomain and extraterminal domain (BET) proteins that regulate gene expression in part through the sequestration of p300 histone acetyltransferase activity and other transcriptional machinery to specific genomic loci (5). MYC is a major target of BET proteins, and NMC cells harboring BRD4-NUT fusions are dependent on MYC for maintenance of an undifferentiated, proliferative state (6,7). Amplification or overexpression of the MYC oncogene is also associated with poor prognosis in other solid tumor types, such as medulloblastoma (8,9), breast cancer (10), ovarian cancer (11), prostate cancer (12), and lung cancer (13).…”
Section: Introductionmentioning
confidence: 99%